Pengaruh Pupuk Organik Cair (POC) Nira Aren dan Limbah Buah Nangka terhadap Pertumbuhan Tanaman Sawi (Brassica juncea L.) dan Beberapa Sifat Kimia Tanah - Sargon, Claudia Maretha Lasmidevi; Soniari, Ni Nengah (Nandur; Vol 2 No 1 (2022), 2022)
The aim of the study was to determine the effect of liquid organic fertilizer application of palm sap and jackfruit waste on the growth of mustard greens and the optimum dose of LOF on mustard greens. The research was carried out from November 2020 - March 2021 in the yard of the house in Carep Village, Langke Rembong District, Manggarai Regency, East Nusa Tenggara with an altitude of 1,171.5 m above sea level and at the Soil and Environment Laboratory, Faculty of Agriculture, Udayana University. The design used in this study was CRD (Completely Randomized Design) with 6 treatments and 4 replications. The LOF dose treatments P0 = 0 ml/l water, P1 = 5 ml/l water, P2 = 10 ml/l water, P3 = 15 ml/l water, P4 = 20 ml/l water and P5 = 25 ml /l water. Parameters observed were plant height, number of leaves, plant fresh weight and plant dry weight, total number of microorganisms in the soil, pH, organic C, total N, available P, available K and soil moisture content. The results showed that the application of liquid organic fertilizer from jackfruit waste on mustard plants (Brassica juncea L.) had a very significant effect on the parameters of available K, moisture content, total microbial population, plant height 21 DAP, fresh plant weight and oven-dried plant weight, gave a significant effect on the parameters of N-total, plant height 14 DAP and 28 DAP and had no significant effect on organic C, soil acidity (pH), available P, plant height 7 DAP. This study has not found the optimum dose because the highest dose treatment (P5) is still increasing.